POSSIBILITY OF APPLICATION OF THE BALANCED SCORECARD AT SMK Sanjaya PAKEM - One, Murniyati; one, Drs. Supardi, MM. (Accounting, 2009)
Achieve organizational goals is not an easy thing. To achieve those objectives required good planning. Without a good plan then the possibility of achieving the goal to be getting smaller. A good plan is not a guarantee of the achievement of objectives. The objective will be achieved if a good plan is executed well too. A good plan must meet certain requirements that one of them is the performance measurement mechanism. With the measurement of performance it will be known whether the company has been operating in the right direction, up to how big the goal can be achieved and so forth. The measurement results can also be used as a basis for granting awards, basic promotion, and punishment. Without a good performance appraisal, the organization did not know whether the organization is correct or not, do not know the possibility of a problem to be faced, even the real problem faced was often not detected. Problems faced by the new note after the problem has become complex and chronic, so to overcome very difficult or even can not be overcome. Without a good performance appraisal system, the achievement of organizational goals or commonly called orgnisasi success is only a coincidence, that at any time can be lost and can not be expected when it will happen again At first, performance measurement is only applied to one aspect, the financial aspect only (for companies) or non-financial aspects of the course (for non-profit organizations). For an organization that aims to profit or corporate performance assessment trandisional just about any financial aspects such as income, income level, the level of gross profit (gross profit margin), ROI (Return On Investment), ROA (Return On Asset), RONA (Return On Net Asset ), ROE (Return On Equity Owners), and so forth. For organizations that are not aimed at profit, performance measurement system is also only about one aspect, the aspect of non-operational or financial. Performance measurement depends on the type of organization, such as the success rate of students (for educational organizations), the level of patient occupancy or occupancy rate (for healthcare organizations) and so forth. Performance measurement is only one aspect is commonly called a traditional performance measurement systems. In the past the system is adequate because the competition is not as tight and seinten now. In today´s performance appraisal as it was not necessary but not sufficient, because it is partial or only some aspects that are measured and also be short term so often sacrifice long-term interests or goals. With such performance measures the organization will not be able to measure the sustainability level of organization, were unable to detect the possibility of problems, and so forth. In other words such a measurement system that contains many weaknesses. The system is only suitable to be applied to the organization that low-level competition. Conditions like this only happened in the past. For now, let alone in times to come the competition in what areas are very strict and complex, and will become increasingly tight and increasingly complex that traditional performance measurement systems are not suitable and not adequate anymore. If the performance measurement system will be retained then thesustainability of the organization will be threatened, which means the organization´s goal is not achieved. Keywords : balanced scorecard